Problem Based Learning (PBL) Effectivenessless in Improving Critical Thinking Ability: Meta-Analysis Study - Vecolitha, Olivia; Yudiarso, Ananta (Universitas Muhammadiyah Metro, 2021)
This meta-analysis research aims to see the effectiveness of problem-based learning (PBL) to increase critical thinking skills. The study involved 20 research journals with 1386 participants. The analysis was carried out using the Meta-mar (Free Online Meta-Analysis Service) website based on the number of samples (N), mean (M), and standard deviation (SD). The analysis results showed that the value of the g random model effect size was -0.58 (95% CI = -0.878 to -0.278, p = 0.0002) with an inconsistency (I2) value of 86.4%. These results indicate that problem-based learning (PBL) has a less significant effect on increasing critical thinking skills.